Massive hemothorax caused by intercostal artery pseudoaneurysm:a case report - Caiyang Liu; Ran Ran; Xiaoliang Li; Gaohua Liu; Chuanxi Wang; Ji Li (Journal of Cardiothoracic Surgery, 2021)
Abstract Background Intercostal artery pseudoaneurysm is rare and at the risk of rupture. The aetiology is always reported to be iatrogenic and traumatic injury. Embolisation is the most common therapeutic method. Here, we report a case of spontaneous intercostal artery pseudoaneurysm and cured by combining covered stent grafting and surgical management. Case presentation A 60-year-old man complained of acute right back pain for 5 h. Computed tomography showed right massive hemothorax and a giant mass with distinct feeding vessel originated from the thoracic aorta within the right hemithorax. Thoracocentesis was performed, and then a covered stent was positioned across the origin of the feeding vessel. The patient was diagnosed with intercostal artery pseudoaneurysm. Finally, we successfully resected the pseudoaneurysm and ligated the proximal part of the artery. Histologic examination have proved the diagnosis. The postoperative course was uneventful, and the patient was discharged on postoperative day 10. There is no recurrence reported during follow-up. Conclusions Spontaneous intercostal artery pseudoaneurysm is extremly rare. Delayed hemothorax due to rupture of the pseudoaneurysm may occur years after the formation. Early diagnosis is important and a combined treatment of endovascular intervention and surgical management is feasible, especially for the case of ruptured large tumour-like mass presentation of the pseudoaneurysm.